Optimalisasi Nilai Komersial Produk Pertanian Kelompok Tani Melalui Pemasaran Digital Untuk Mendukung Program Patuwen Kopi - Irawan, Paulus Lucky Tirma; Windra Swastika; Sultan Arif Rahmadianto (Jurnal Atma Inovasia, 2025)
The Patuwen Kopi program initiated by Gereja Kristen Jawi Wetan (GKJW) involves four coffee farmer groups in Malang and Jombang that face significant challenges in product marketing. The primary problems include limited marketing access, dependency on middlemen, and lack of knowledge about digital marketing strategies, resulting in declining economic value of coffee products. This study aims to optimize the commercial value of agricultural products through the development of a website-based digital marketing platform to support the sustainability of the Patuwen Kopi program. The research employed Participatory Rural Appraisal (PRA) methodology consisting of four stages: problem identification using 5 Whys technique, community needs identification, determination of alternative solutions and problem-handling priorities, and identification of ideal solutions. This approach ensures active participation of farmer groups in formulating sustainable solutions. The study successfully developed an e-commerce website application with five main features: landing page for digital marketing media, product page for catalog and ordering, article page for community branding, admin page for dynamic content management, and transactional page for sales recording. The website is integrated with WhatsApp to facilitate communication and transactions, equipped with monthly sales reporting system. The developed digital platform successfully meets the needs of farmer groups in terms of digital marketing, community branding, and transaction recording. The application has undergone limited testing and meets community expectations to support the Patuwen Kopi program, with potential for further development according to future business needs.